Maximum resolution of switched capacitor converter: a graphical approach - Sara Khalid Natheer; Mohamad Natiq Abdul Kadir (Institute of Advanced Engineering and Science, 2022)
The efficiency of a switched capacitor converter can be represented as the ratio of the output voltage to open-circuit voltage. Switched capacitor converters with adjustable gain are designed with multiple no-load voltages to obtain higher efficiency over the voltage control range. This paper aims to realize the maximum resolution of a switched capacitor converter. A graphical representation of the output voltages formation has been proposed. The voltage composition diagram reveals a switching pattern of the multiphase operation cycle that leads to the desired output voltage. The proposed method has been applied to determine all possible output voltage levels that lead to maximum resolution. A three-capacitor converter has been controlled with the proposed scheme. The simulation results show that the output voltage follows the reference voltage closely. The converter provides 60% more output voltage steps compared to the nearest comparable design in the literature.